Neuroform EZ stenting for basilar artery atherosclerotic stenosis - Jingfeng Duan; Jiawei He; Yanbing Wen; Jiabing Huang; Liyan Li; Jun Yin; Dongxu Qiu (Scientific Reports)
Abstract Periprocedural complications, including perforator occlusion, in-stent restenosis, and even death, are frequently encountered in endovascular therapy for basilar artery (BA) lesions. This study sought to evaluate the efficacy of the Neuroform EZ stent in managing atherosclerotic BA stenosis. A retrospective analysis was conducted on clinical data from 71 patients with symptomatic atherosclerotic BA stenosis who underwent Neuroform EZ stent implantation. The primary outcomes assessed were periprocedural complications (ischemic stroke, death, restenosis, or hemorrhagic stroke) within 30 days post-surgery. Additionally, multivariable logistic regression analysis was used to identify risk factors for in-stent restenosis (ISR). Results showed that the mean stenosis degree significantly improved from 85.2% ± 8.7% before treatment to 25.8% ± 12.5% after Neuroform EZ stent placement. Furthermore, the mean NIHSS score decreased by 3 points following the procedure. The overall ISR rate among all patients was 6.5%. Multivariable logistic regression analysis revealed that irregular post-procedural antiplatelet therapy (HR, 3.231; 95% CI, 1.09–4.61; p = 0.031), lesion length (HR, 2.966; 95% CI, 1.21–4.23; p = 0.026), and lesion location (HR, 3.117; 95% CI, 1.12–4.15; p = 0.042) were independent risk factors for long-term ISR. In conclusion, this study provides evidence supporting the effective use of the Neuroform EZ stent in the treatment of refractory BA stenosis.